Mise en œuvre du plan d’intervention : continuités et ruptures de l’identité professionnelle enseignante dans une école secondaire du Québec - Joannie St-Pierre (Éducation et Socialisation)
Individualized education programs are a mechanism enabling inclusive practices and the transformation of teachers’ work. An autoethnography conducted as part of my doctoral thesis revealed fluctuations in professional identity. The data collected in a Quebec high school prompt us to reflect on the dynamics of identity and the singularity that weakens the sense of belonging to the profession, and idealizes certain individual aspects.